Stoic Management and Philosophy: Resilience and Stress Management in the Workplace - Gleydis Harwida; Novilia, Evita; Winarno, Agung (International Journal of Integrative Sciences, 2024)
This research examines the relationship between the principles of Stoic philosophy and their application in a management context, specifically in terms of resilience and stress management in the workplace. Stoic philosophy, which flourished in Ancient Greece and Rome, offers a view of life that can help individuals face life's challenges with poise and wisdom. Using the literature review research method, this article analyzes various studies and theories that link Stoic teachings to modern management, as well as how Stoic principles can be applied to increase mental resilience, reduce stress, and promote well-being in the workplace. This research aims to provide insight into the relevance of Stoic philosophy in improving managerial effectiveness and workers' psychological well-being